2011
DOI: 10.1136/gutjnl-2011-300219
|View full text |Cite
|
Sign up to set email alerts
|

The Manitoba Inflammatory Bowel Disease Cohort Study: a prospective longitudinal evaluation of the use of complementary and alternative medicine services and products

Abstract: Those with IBD commonly try CAM, although very few use these approaches regularly over the years. CAM is not usually used by patients with IBD for disease management, but clinicians should be aware that many will test the services and products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 37 publications
(41 reference statements)
10
42
1
Order By: Relevance
“…Gender differences are commonly reported in previous studies of CAM use, both in general populations and in IBD populations [1,10,12,14,15]. Additionally, those who were married reported higher CAM use compared to unmarried.…”
Section: Discussionmentioning
confidence: 66%
“…Gender differences are commonly reported in previous studies of CAM use, both in general populations and in IBD populations [1,10,12,14,15]. Additionally, those who were married reported higher CAM use compared to unmarried.…”
Section: Discussionmentioning
confidence: 66%
“…Earlier studies were referral center based, 12,17,18,20,[30][31][32][33][34][35][36] which can lead to overrepresentation of patients with more severe disease or lacked comparison with control subjects from the general population. 11,12,14,15,[17][18][19][20]22,[32][33][34][35][36][37] Because of our large sample size, we were able to conduct subgroup analyses while maintaining statistical robustness. Also, because more than 90% of patients with IBD in Canterbury were included in the study, the results are more likely to be more generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that CAM use in patients with IBD may be associated with younger age, [17][18][19][20] female gender, 11,12,21 higher education, 14,20 and higher disease severity. 19,22 However, the majority of these studies used a small study population, lacked comparison with a control group, and were referral center based.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We have previously reported that in our Manitoba IBD Cohort Study, 40% of patients have used CAM at some time point to help in the treatment of their IBD. 18 It would likely require a prospective study to inquire of persons using CAM as to whether they are using it instead of conventional medications.…”
Section: Discussionmentioning
confidence: 99%